implementasi penggunaan alat peraga karton berpetak terhadap hasil belajar matematika siswa kelas 3 SDN Bojongrenged VI - Sifa Nursinah; Ina Magdalena; Sa’odah Sa’odah (STKIP Singkawang, 2020)
This research was a descriptive qualitative with a titled implementation of cardboard display tools based on the study of mathematics in primary school with 3rd grade students of S dn Bojong renged IV. The research subject are 3rd students of Sdn Bojong renged VI This research aimed to “how to implemented of cardboard display tools based on the study of mathematics in primary school with subjects are 3rd grade students of Sdn Bojong renged VI.? The method of this research are qualitative data which is the instruments used in this study are observation, interviews, and documentation. The research objective is that the implementation of the use of teaching aids can provide concrete scientific contributions to the implementation of learning outcomes, especially in mathematics. The data was then analyzed using qualitative descriptive.Based on the results of the study, it can be concluded that both the process assessments and the learning assessments made by submitting post tests are improvement in students studies. In the last data, Students reached 34,78 percent which is just 8 of 23 children who have been got the same grade with a value of test results above KKM and 65,22 percent which is just 15 of 23 children who have been got below KKM. The minimum criteria (KKM) of this lesson is 60. The students who have a score below KKM just 10 of 23 children that be sampled. The results of students in math studies from the post-test in fraction sub are increase